ROLE OF ISLAMIC TRADITIONAL IN ISLAMIC RELIGIOUS EDUCATION TO ADRESS DEATH ANXIETY AMONG ELDERLY HOME CARE RESIDENTS IN YOGYAKARTA - Muhammad Rizai; Zulkipli Lessy (Lembaga Penelitian Universitas Pasundan, 2022)
The number of population of older people has risen over time. The older adults’ latent problems tremendously vary, and one of the biggest challenges for them is having anxiety about death. For this reason, it is vital to accurately identify contributing factors and then Islamic religious instructors seek a favorable treatment for encountering the problem. The lack of understanding of Islamic teachings related self is one of causal factors in this case. This study used a qualitative analysis and descriptive design with the research subject of elderly people at Budi Luhur Social Service Center (BPSTW) Budi Luhur, Kasihan, Bantul, Yogyakarta Special Region. The research sample was classified into two categories: females and the were participating in the Islamic religious teaching program. Data were collected through interview, observation, documentation of relevant written texts, and the data were analyzed using a triangulation technique. The study found that lecturing, question and answer, and private-informal conversations were effective techniques for the understanding of Islamic teachings throughout the course in regards with oneself towards dying and death.